2020
DOI: 10.3390/atmos11030252
|View full text |Cite
|
Sign up to set email alerts
|

Skill Assessment of an Atmosphere–Wave Regional Coupled Model over the East China Sea with a Focus on Typhoons

Abstract: This study performed several sensitivity experiments to investigate the impact of atmosphere–wave coupling on the simulated wind and waves over the East China Sea (ECS) with a focus on typhoon events. These experiments include stand-alone regional atmosphere model (CCLM) simulations, stand-alone spectral wave model (WAM) simulations driven by the regional atmospheric model CCLM or ERA5 reanalysis, and two-way (CCLM-WAM) coupled simulations. We assessed the simulated wind speed and significant wave height again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Furthermore, Ramon et al (2019) revealed that ERA5 features the best agreement with the observations among five global reanalyses for the mean wind speed and wind variability at turbine hub heights. By comparing against satellite and station observations, Li et al (2020) showed that ERA5 features high quality in capturing surface wind conditions over the East China Sea, with bias less than 0.4 m/s. All of the above support the reasonability of using ERA5 as a reference data set in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Ramon et al (2019) revealed that ERA5 features the best agreement with the observations among five global reanalyses for the mean wind speed and wind variability at turbine hub heights. By comparing against satellite and station observations, Li et al (2020) showed that ERA5 features high quality in capturing surface wind conditions over the East China Sea, with bias less than 0.4 m/s. All of the above support the reasonability of using ERA5 as a reference data set in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The atmospheric model used herein is the Consortium for Small-Scale Modeling (COSMO)-Climate Mode (CLM) (CCLM) regional climate model (Rockel et al, 2008;Doms and Baldauf, 2013). CCLM is the community model of the German regional climate research community and has already been utilized in several studies employing coupled systems with waves (e.g., Cavaleri et al, 2012b;Wahle et al, 2017;Li et al, 2020) or oceanic and other earth system components (e.g., Ho-Hagemann et al, 2013, 2015, 2017Van Pham et al, 2014;Will et al, 2017;Kelemen et al, 2019). CCLM is based on the primitive thermo-hydrodynamical equations describing a compressible flow in a moist atmosphere.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The wave model utilized in this study is the third-generation WAve Model WAM (WAMDI Group, 1988;ECMWF, 2019). WAM has also been used successfully in several studies that assessed the wave-atmosphere coupling together with CCLM (e.g., Cavaleri et al, 2012b;Wahle et al, 2017;Li et al, 2020). However, WAM has also been employed with other atmospheric models, such as the ECMWF model (e.g., Janssen and Viterbo, 1996;Janssen et al, 2002) or the Weather Research and Forecasting (WRF) model (e.g., Wu et al, 2017).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…1 We conducted wave hindcast simulations over the NWP and BYE forced by ERA5 wind speed (0.25 • , Hersbach et al, 2020) during 1979-2019 to validate the model's ability to capture the wave climate features in the BYE (thereafter ERA5 driven wave hindcast). ERA5 winds have proved to be robust in forcing wave conditions in the study domain (Li et al, 2020). To study the impact of climate change on wave climate, nested WAM simulations are forced by 3-hourly wind outputs (0.22 • ) from the CCLM-MPIESM RCM simulations (Kim et al, 2020) for the historical climate period and two future periods (2021-2050 and 2071-2100) under the RCP2.6 and RCP8.5 emission scenarios.…”
Section: Methodology and Datasets Wave Dynamical Downscalingmentioning
confidence: 99%